2020
DOI: 10.3390/microorganisms8060824
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Establishes Persistent Infection in Lung Microvascular Endothelial Cells and Primes a Th2-Skewed Immune Response

Abstract: Human Metapneumovirus (HMPV) is a major cause of lower respiratory tract infections. HMPV infection has been hypothesized to alter dendritic cell (DC) immune response; however, many questions regarding HMPV pathogenesis within the infected lung remain unanswered. Here, we show that HMPV productively infects human lung microvascular endothelial cells (L-HMVECs). The release of infectious virus occurs for up to more than 30 days of culture without producing overt cytopathic effects and medium derived from persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…However, ischemic stroke after COVID-19 infection has been proposed to be multifactorial in nature, including the development of a cytokine storm, activation of the innate immune system, embolic events triggered by pre-existing or new-onset arrhythmias, hypoxia-induced ischemia secondary to severe pulmonary disease, thrombotic microangiopathy, and direct infection of the brain endothelium that causes viral-induced vasculitis (Zakeri et al 2021). Notably, a recent report found that hMPV could infect both microvascular endothelial cells and lung epithelial cells, and that these cells induced immune responses (Bugatti et al 2020). hMPV can attach to many cell surface receptors before entering the cells; the viral receptors include heparan sulfate, arginine-glycine-aspartate (RGD)-binding integrins, and other protease-sensitive surface proteins (Cox and Williams 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, ischemic stroke after COVID-19 infection has been proposed to be multifactorial in nature, including the development of a cytokine storm, activation of the innate immune system, embolic events triggered by pre-existing or new-onset arrhythmias, hypoxia-induced ischemia secondary to severe pulmonary disease, thrombotic microangiopathy, and direct infection of the brain endothelium that causes viral-induced vasculitis (Zakeri et al 2021). Notably, a recent report found that hMPV could infect both microvascular endothelial cells and lung epithelial cells, and that these cells induced immune responses (Bugatti et al 2020). hMPV can attach to many cell surface receptors before entering the cells; the viral receptors include heparan sulfate, arginine-glycine-aspartate (RGD)-binding integrins, and other protease-sensitive surface proteins (Cox and Williams 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%